Fornos para fusão e espera para indústria de alumínio : caracterização de materiais refratários e conservação de energia - Novo, Marcela Munhoz Monteiro (2012)
The industrial need to reduce energy consumption is part of a continuous evolution towards higher levels of sustainability and competitiveness. Considering these aspects, the search for alternatives to improve the performance of melting and holding furnaces in the aluminum industry is directly dependent on the refractory materials ability to keep heat and withstand the mechanical, chemical and thermal degradation processes. Therefore, five dense high-alumina commercial refractories were characterized according to their thermo-mechanical properties, physical features and aluminum corrosion resistance. The results pointed out that choosing the most suitable composition requires the evaluation of the chemical aspects and thermal shock resistance. Moreover, the understanding of high emissivity coatings applications was also focused in order to develop an alternative which could increase heat savings. Thus, two methods were developed to analyze the coating efficiency: a) the temperature measurement of painted specimens fired at different temperatures in a furnace; and b) the heating curve profile of a ceramic sample during firing in a furnace lined with refractories previously coated with high emissivity paint. Three commercial products were characterized and both evaluation methods showed that the high emissivity coating affected the sample heating, although a reduction in its efficiency was observed during the testing cycles. Furthermore, in order to attest the effectiveness in industrial practices, a high emissivity coating was applied on the refractory walls of a melting aluminum transport crucible. The results showed that the combined analysis involving the correct selection of refractories and application of high emissivity coatings can open new paths toward cost reduction and industrial sustainability.